Isolation and identification of bacterial flora from respiratory tract of healthy horses - Muktha, ZB; Kabir, SML; Rahman, MT (Journal of the Bangladesh Agricultural University, 2016)
This study was carried out during the period of July to December, 2014 in order to isolate and characterize bacterial flora present in the respiratory tract of healthy horses in and around BAU campus. Eighteen apparently healthy horses were used for the study. Swab samples were collected from the nasal cavity. The bacteria was isolated ,identified and characterized by cultural (aerobic condition),staining, biochemical and PCR technique. Each of the samples collected yielded at least one bacterial species. A total of 27 bacteria were isolated from the selected animals. The majority of the isolates (15/27, 55.56%) were Gram-positive and the rest (12/27, 44.44%) were Gram-negative. Bacterial isolates were Staphylococcus aureus (83.33%) and E. coli (66.66%).The antimicrobial susceptibility pattern of bacterial isolates was investigated by disc diffusion method. The antibiotic sensitivity test of Staphylococcus aureus revealed that the isolates were highly sensitive to ciprofloxacin, moderately sensitive to gentamicin and resistance to amoxicilin, ampicilin and erythromycin. On the other hand, E. coli showed moderately sensitive to ciprofloxacin and gentamycin, mildly sensitive to erythromycin and resistance to amoxicilin and ampicilin. Detection of E. coli and S. aureus from the respiratory tract of healthy horses were not unexpected. Ciprofloxacin and gentamicin could be used for therapeutic purpose, if diseases occur by these organisms in horses. J. Bangladesh Agril. Univ. 13(2): 239-246, December 2015